Pembangunan Sosial dalam Kartu Jakarta Pintar: Menakar Kebijakan Pemerataan Pendidikan bagi Warga Jakarta - Nurhayati, Cucu; Ikhsan, A. Bakir (Jurnal Sosiologi Andalas, 2025)
The Jakarta Smart Card (KJP) is a governmental program in Jakarta designed to promote educational equity for students from economically disadvantaged backgrounds. This KJP initiative represents a key governmental policy, structured as a social development instrument. This policy serves as an appropriate measure to ensure educational equality. Hence, what kind of policy concept should the government adopt to promote equitable education for the people of Jakarta? This study aims to provide a new policy direction for the government's efforts in social development within the education sector, specifically through the KJP program in Jakarta. The study utilizes a mixed-methods approach, employing both quantitative and qualitative research to capture the structural, cultural, and social process dimensions related to the effectiveness and implementation of the KJP within the community. The quantitative research involved a random sampling of 99 respondents. The qualitative component employed a snowball sampling technique through in-depth interviews with 11 informants. The findings reveal several key results: First, structurally, the KJP is deemed effective as a program for enhancing community education and has demonstrably reduced the school dropout rate. Second, culturally, the KJP has successfully motivated new values and enthusiasm within the community, encouraging greater diligence, effort, and responsibility. Third, the KJP program was socialized and communicated transparently through schools and a dedicated website, as a form of social process. The concept of social development, framed by the dimensions of structure, culture, and social process, emerges as the appropriate and effective solution for achieving inclusive and holistic educational equity